Pemanfaatan Modifikasi Mosquito Killer Sebagai Alternatif Pengendalian Nyamuk Aedes Aegypti: Utilization of Modified Mosquito Killer as an Alternative for Aedes Aegypti Mosquito Control - Eni Rizki Rahayu; Dewi Atikah; Agus Setiyadi; Fajar Adhie Sulistyo; Sasni Triana Putri; Sariaman Purba; Utami Sulistyaningsih (Journal of Health, 2023)
Dengue hemorrhagic fever is a major global problem, with 2.5 to 3 billion people at risk of developing the disease. Aedes aegypti is the main vector in epidemics, a disease that usually affects urban areas, but is starting to hit rural areas, infecting an estimated 50 to 100 million people each year. The only program to control it is mosquito control as a vector. This study aims to determine the effectiveness of using modified mosquito killer as an alternative to controlling Aedes Aegypti mosquitoes. The method in this study was an experiment with a pretest-posttest design. The research was conducted in July-September 2022. The population in this study was 34 houses of residents suffering from DHF in the Sindang Barang Health Center, Bogor City. The sampling technique in this study used the sowball sampling technique. The procedure in this study used UV light to attract mosquitoes and fan suction to attract mosquitoes into the trap then assessed changes in the density of Aedes Aegypti mosquitoes using observation sheets and hand counters using measuring instruments, namely changes in the number of mosquitoes trapped and killed in units. tail at 10.00-11.00 WIB. The results of the pretest-posttest data show that the density of mosquitoes has a significance value of 0.053. So it can be concluded that the use of a modified mosquito killer is not effective as an alternative to controlling Aedes aegypti mosquitoes. The use of mosquito killers depends on humidity and temperature factors.